E-learning as a university challenge of the 21st century - Stradomska, Marlena (Kultura-Społeczeństwo-Edukacja, 2021)
The article is one of several articles summarizing research carried out with a group of foreign students who come to Poland to participate in the Erasmus+ program. Method and research group: Research has been taking place since 2016 and is conducted using an interactive Google survey. The study group consists of 128 people aged 18 to 25 years. The respondents chose Poland, specifically the Maria Curie-Skłodowska University, in order to complete a semester or an academic year. This article will also present structured interviews that were conducted with foreign students. Aim of the study: To learn about the attitude of foreign students towards modern teaching methods (e-learning). An additional goal was to verify the knowledge regarding this method of education and to compare Poland with the respondents’ home countries. Results: The respondents come from European countries such as Spain, Portugal, Germany, France, as well as, Brazil and India. Most of them appreciate the possibilities of e-learning (87%). Over half of the respondents (62%) say that in Poland distance learning was rather not implemented until 2020. What changed this situation was the coronavirus outbreak. In social sciences, they also appreciate the possibility of classes in the traditional form due to the possibility of participating in workshops and specialist training, or giving presentations.